The bear in ancient Mesopotamia - Verderame , Lorenzo (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2024)
Among the animals documented in archaeological and epigraphic sources from ancient Mesopotamia, the bear has received little or no attention. This contribution aims to fill this gap by providing an overview of all the available sources –textual, archaeozoological and iconographical– and discussing the relationships between bears and the human community.